2015
DOI: 10.1186/s12893-015-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid to scrotal fistula secondary to mesh erosion: a rare complication of inguinal hernia repair in a patient on anticoagulation

Abstract: BackgroundFew reports from the medical literature have presented severe mesh-related complications following laparoscopic repair of inguinal hernia. One of these complications is being mesh erosion into bowel, resulting in fistulous tract with subsequent abscess formation.Case presentationA 75-year-old patient, status post laparoscopic bilateral inguinal hernia repair, and on anticoagulation for dual prosthetic heart valves, presented with a unique case of sigmoid to scrotal fistula, post mesh erosion, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The role of diverticulosis in the fistula formation remains unclear. There are cases in which diverticular disease coexisted with mesh-related fistulae, although no direct implication could be noted [7][8][9][10][11]. However, the presence of diverticula is speculated to be a risk factor [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of diverticulosis in the fistula formation remains unclear. There are cases in which diverticular disease coexisted with mesh-related fistulae, although no direct implication could be noted [7][8][9][10][11]. However, the presence of diverticula is speculated to be a risk factor [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the second case, the mesh had eroded through the wall of the sigmoid colon eventually leading to the formation of a colocutaneous fistula, requiring open laparotomy with sigmoidectomy and en bloc excision of the adherent mesh. In such cases, where mesh erosion coexists with diverticular disease, diagnostic dilemmas may arise, nevertheless, surgery effectively addresses both the colocutaneous fistula and the required excision of the inflammatory mass containing the mesh [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…A Degheili et al reported a sigmoid to scrotal fistula post inguinal hernia repair in 2015. 10 We found just one comparative study about early and late-onset prosthetic mesh infection published in 2015 by Wengcheng Kong et al 11 Very few case reports or research articles were found on ECF following open incisional hernia repair. [12][13][14] For prevention of fistulas, Losanoff et al proposed using tissue impervious composite material in close proximity of bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Pore size, filament structure, and the surface of the mesh structure are decisive in how much adhesion is produced when the mesh is placed in the vicinity of the bowel. Microporous structure at the side of the bowel and additional surface [58] in composite meshes provide a temporary barrier against adhesion. However, the absorbable coatings may be degraded in the short term [59].…”
Section: Adhesionmentioning
confidence: 99%